TINDAK PERLOKUSI TERHADAP TINDAK TUTUR EKSPRESIF MENGELUH (KAJIAN PRAGMATIK) - Nurul Inayah Fauziah (Jurnal Sastra - Studi Ilmiah Sastra, 2019)
This study aims to identify expressive speech act with the meaning of complaining, to find out the complain strategy and perlocution act on expressive act of expression with complain strategy used on the object of study. The method used in this study is a descriptive research method. The author uses the record method and records it in the provision of data, then analyzed using contextual methods and the results of the analysis are presented in an informal method. To determine expressive speech acts with the meaning of complaining, complaining strategy and perlocution act using theory of Urawa, Trosborg and Levinson. The object of the study used in this study is drama Great Teacher Onizuka (2012).According to the analysis of data, there are three results which are found: (1) expressive act of complain has 4 classification of meaning, such as: dissatisfied, suffering, loss and disappointment. The most dominant meaning of complain is a disappointment. (2) the complain strategy that is widely used is the strategy of complaining direct allegations. (3) the most dominant perlocution act is negative responsive.